VLSI digital signal processors an introduction to rapid prototyping and design synthesis - Madisetti, Vijay K. (IEEE Press Butterworth-Heinemann, 1995)
This is the only book that offers a thorough treatment of the following: design and application of programmable digital signal processors; formal specification and optimization of signal processing architectures and circuits; high-level synthesis of DSP architectures and datapaths; detailed treatment of application-specific integrated circuits (ASICs); scheduling, allocation and assignment algorithms for multiple processor DSP systems; and hardware/software co-design issues in DSP. VLSI Digital Signal Processors: An Introduction to Rapid Prototyping and Design Synthesis provides a cohesive, quantitative and clear exposition of the implementation and prototyping of digital signal processing algorithms on programmable signal processors, parallel processing systems and application-specific ICs. Included are both programmable and dedicated digital signal processors, and discussions of the latest optimization methods and the use of computer-aided-design techniques.